Students’ Perception of Learning Management System Supported Smartphone: Satisfaction Analysis in Online Physics Learning (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Learning Management System Supported Smartphone (LMS3) is a new and innovative application in online physics learning synchronously. The research aims to investigate the level of students’ satisfaction in using LMS3 and determine predictor variables that affect the level of students’ satisfaction. A descriptive study with survey method was implemented to 71 physics education students who attended online physics learning. The instrument in this research was a Students’ Satisfaction of LMS3 Questionnaire (S2LMS3Q). The average percentage determined the level of student’s satisfaction, and multiple correlations and multiple regressions determined the predictor variables. The level of satisfaction in using LMS3 reached a high level with an average of 76.03%. At the 0.01 significance level, the adjusted R2 value of four predictor variables was 0.393. The multiple correlation analysis showed β for each predictor variable were 0.34 for gender, 0.07 for age, 0.43 for experience in using LMS, and 0.13 for internet connection. In conclusion, the level of students’ satisfaction was high, and the most influential predictor variables were the experience in using LMS and age. This study suggests an in-depth evaluation of online learning through students’ perceptions in order to improve the quality of further learning.